Penerapan Model Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Hasil Belajar Matematika Siswa - Abdul Latif; Haryati Ahda Nasution; Desniarti Desniarti; Ummi Aulia; Afifah Tamimi (Departement of Mathematics Education, 2024)
This research is motivated by low student learning outcomes caused by minimal interaction between students and lack of active participation in the learning process. As part of our endeavour to enhance classroom learning, we seek to assess how the Make a Match cooperative learning paradigm affects students' arithmetic ability. Classroom Action Research (PTK) is the methodology used. The academic year 2024–2025 saw the research team from SMA Negeri 10 Medan doing their studies, with the research subjects being class XI IPA 4 students, namely 33 students, consisting of 13 men and 20 women. The research results show an increase in learning outcomes, especially in the material Deriving Algebraic Functions. In cycle I, 20 students achieved the KKM score (≥75) and 13 students did not achieve it. In cycle II, 26 students reached the KKM and 7 students did not. There was an increase of 18.18% from 6 students who previously did not reach the KKM. This shows the effectiveness of the Make a match cooperative learning model in improving student learning outcomes.